Occurrence of adverse events among patients with inflammatory bowel disease in the HealthCore Integrated Research Database. (2nd September 2015) - McAuliffe, Megan E.; Lanes, Stephan; Leach, Timothy; Parikh, Asit; Faich, Gerald; Porter, Jane; Holick, Crystal; Esposito, Daina; Zhao, Yueqin; Fox, Irving
Abstract: Objectives: Inflammatory bowel disease (IBD) is a chronic condition commonly requiring lifelong care. Both IBD and IBD-related treatments can cause significant morbidity, and it is often difficult to differentiate their relative etiologic contribution to adverse events (AEs). The objectives of this study were to assess the rates of select AEs among patients with IBD as a function of disease severity and of the use of anti-tumor necrosis factor alpha (anti-TNFα) medications. Methods: We conducted a retrospective cohort study of IBD patients in the HealthCore Integrated Research Database (HIRD TM ) between January 2004 and January 2011 to determine rates of AEs in patients with mild and moderate to severe IBD. Key study endpoints were select prespecified malignant neoplasms, infections, and other AEs of interest. Results: A total of 33, 386 IBD patients (52.7% ulcerative colitis; 47.3% Crohn's disease) met the inclusion criteria, and 60% had been followed for ≥1 year. Patients with moderate to severe IBD had increased rates of infections, lymphatic and digestive tract cancers, gastrointestinal (GI) perforations, and myocardial infarctions versus patients with mild IBD. Patients with IBD who used anti-TNFα therapies during the study had increased incidence of many types of infections, certain GI cancers (including rectal and anal cancer), intestinal perforations, and kidney stones compared with patients who had never used anti-TNFα therapies. Conclusions: Results from this large US cohort provide descriptive information on AE rates in a population of IBD patients undergoing routine care, estimating background incidence rates of AEs that are not readily available in the published literature. Our study findings may be limited owing to a lack of generalizability and potential for misclassification due to reliance on medical diagnosis and treatment and procedure codes to identify disease, comorbidities, and treatments. Further research and validation of our findings in other populations and databases are needed.